A rereading of A Bolívar by Luis Alberto Sánchez - Kapsoli Escudero, Wilfredo (2024)
In this essay, the author rereads Sánchez's work, historically contextualizing the novel with its main protagonists and actions carried out in favor of Peruvian independence. In this work the figures of Simón Bolívar, Manuelita Sáenz, José de San Martín and José Antonio de Sucre stand out. Guerrillas from the central mountains such as Ignacio Quispe Ninavilca, Isidoro Villar, José Antonio Manrique and Fray Bruno Terreros, a Franciscan priest who commanded a guerrilla in Jauja and later joined the liberating army, also act in different roles.